WORKSHOP EFEKTIVITAS KETERAMPILAN BERBICARA MENGGUNAKAN MODEL PAIRED STORYTELLING SEKOLAH DASAR - Elvima Nofrianni; Opi Andriani (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
This Community Service (PKM) was carried out at SDN 103/II Tanjung Agung, Muara Bungo Regency. Partner problems are (1) Lack of student activity in speaking, (2) Lack of self-confidence and courage in the learning process in class. (3) Teachers do not interact enough with students and do not use exciting and varied learning models. This PKM aims to provide solutions for partners, namely teachers at SDN 103/II Tanjung Agung, Muara Bungo Regency, to increase the effectiveness of speaking skills using the elementary school paired storytelling model. The method for implementing PKM is carried out by (1) Lecture Method, (2) Learning discussions, and (3) Simulation of the effectiveness of speaking skills using the elementary school paired storytelling model. The PKM results were a workshop on the effectiveness of speaking skills using the elementary school paired storytelling model. The results of the participant response sheet stated that the results were very good, especially for class teachers, so that learning has variations in utilizing learning models.